2010
DOI: 10.2478/v10045-010-0017-1
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Seed-Borne Sarocladium Oryzae, the Incitant of Rice Sheath Rot on Rice Seed Quality

Abstract: Effect of Seed-BorneSarocladium Oryzae, the Incitant of Rice Sheath Rot on Rice Seed QualityRice seeds collected fromSarocladium oryzaeinoculated plants produced more discoloured grain, chaffiness and recorded much lower seed germination than seeds collected from healthy plants in all the three cultivars tested. The germination, chaffiness and discolouration in healthy plants were found to be in the range of 70.50 to 93.50 per cent, 5.5 to 17.75 per cent and 4 to 18 per cent respectively. There was a progressi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 4 publications
0
10
0
1
Order By: Relevance
“…Though the most described virulence factors of S. oryzae are helvolic acid and cerulenin, the fungus also produces cellulolytic, proteolytic, pectinolytic, and oxidative enzymes that play a role in pathogenicity ( Joe and Manibhushanrao, 1995 ; Pearce et al, 2001 ). Gopalakrishnan et al (2010) observed a pronounced decrease in sugar, starch and protein and an increase in phenol content in rice seeds infected with S. oryzae. This probably explains why infected grains are chaffy and germinate poorly.…”
Section: Sarocladium Oryzae: the Major Fungal Rice Sheath Romentioning
confidence: 83%
See 1 more Smart Citation
“…Though the most described virulence factors of S. oryzae are helvolic acid and cerulenin, the fungus also produces cellulolytic, proteolytic, pectinolytic, and oxidative enzymes that play a role in pathogenicity ( Joe and Manibhushanrao, 1995 ; Pearce et al, 2001 ). Gopalakrishnan et al (2010) observed a pronounced decrease in sugar, starch and protein and an increase in phenol content in rice seeds infected with S. oryzae. This probably explains why infected grains are chaffy and germinate poorly.…”
Section: Sarocladium Oryzae: the Major Fungal Rice Sheath Romentioning
confidence: 83%
“…The major symptoms describing rice sheath rot caused by S. oryzae are the following, according to Ou (1985) : the rot occurs on the uppermost leaf sheaths enclosing the young panicles; the lesions start as oblong or somewhat irregular spots, 0.5–1.5 cm long, with brown margins and gray centers, or they may be grayish brown throughout; they enlarge and often coalesce and may cover most of the leaf sheath; the young panicles remain within the sheath or only partially emerge; an abundant whitish powdery growth may be found inside affected sheaths and young panicles are rotted. S. oryzae infection results in chaffy, discolored grains, and affects the viability and nutritional value of seeds ( Sakthivel, 2001 ; Gopalakrishnan et al, 2010 ). The major symptoms of rice sheath rot incited by S. oryzae are presented in Figure 3 .…”
Section: Sarocladium Oryzae: the Major Fungal Rice Sheath Romentioning
confidence: 99%
“…cerulenin and helvoic acid [6][7][8][9] and whole genome sequencing of S. oryzae from our group revealed genes involved in production of cerulenin and helvoic acid 10 . These phytotoxins are responsible for production of greyish-brown necrotic lesion in flag leaf sheath and restricts translocation of photosynthates to the developing panicles, causing quantitative (chaffy grains) and qualitative yield loss including discolouration of grains, reduced seed viability, nutritional and market value 8,11 . Incidence of sheath rot disease is highly correlated with sucking pests 12 , cooler climate with high humidity 13,14 and moisture stress during reproductive stages in aerobic condition.…”
mentioning
confidence: 99%
“…Gejala awal adalah berupa lesi berwarna coklat keabuabuan pada daun bendera (Ou, 1985). Infeksi jamur pada daun bendera bagian atas yang terdapat malai muda dapat mengakibatkan pembentukan malai menjadi terhambat sehingga hanya menghasilkan sedikit biji atau bahkan menyebabkan malai tidak keluar (Chien & Huang, 1979;Gopalakrishnan et al, 2010). Biji yang terinfeksi akan berubah warna dan menjadi steril sehingga hasil gabah dan kualitas biji menjadi menurun, demikian juga dengan viabilitas benih dan nilai gizi beras akan berkurang (Ayyadurai et al, 2005;Mew & Gonzales, 2002).…”
Section: Pendahuluanunclassified